La necesidad de reformar el Código De Trabajo Ecuatoriano, en relación a la igualdad de beneficios para operarios y aprendices artesanales - Luis Humberto Palacios Ortega (2015)
This thesis aims to expose the unconstitutionality of the refusal to allow operators and apprentice craft workshops, receive payment of additional remuneration, an express right of workers, which is determined in the current Constitution and treaties and conventions. So as to support the defense position operators and craft apprentices, performed the analysis of labor law, the craftsmanship and the provisions in the Labour Code of Ecuador, with respect to additional compensation. At the same time, surveys were conducted both workers, employers, the Labour Judges and Lawyers in free exercise, the results were tabulated, graphed, analyzed and interpreted, which follows the verification of the idea to defend. Based on objective data and verification of the idea to defend, we proceeded to issue the necessary conclusions and recommendations, to finally make purposeful framework, which sets out the reasons for the reform of the Labour Code with the repeal of corresponding Article 115